Prenatal diagnosis of colpocephaly with absent corpus callosum. Issue 1 (February 2015) - Ansary, Althaf; Manjunatha, CM; Ibhanesebhor, Samuel
Colpocephaly is a rare abnormality of the brain, described as persistence of primitive foetal configuration of lateral ventricles. It has been found in association with several abnormalities of the brain. Herein we report a case of colpocephaly with absent corpus callosum, confirmed antenatally with foetal MRI following diagnostic suspicion based on absent septum pellucidum at prenatal sonography.